Brain structural concomitants of resting state heart rate variability in the young and old: evidence from two independent samples - Yoo, Hyun Joo; Koenig, Julian (Brain structure & function, 2018)
Previous research has shown associations between brain structure and resting state high-frequency heart rate variability (HF HRV). Age affects both brain structure and HF HRV. Therefore, we sought to examine the relationship between brain structure and HF HRV as a function of age. Data from two independent studies were used for the present analysis. Study 1 included 19 older adults (10 males, age range 62-78 years) and 19 younger adults (12 males, age range 19-37). Study 2 included 23 older adults (12 males; age range 55-75) and 27 younger adults (17 males; age range 18-34). The root-mean-square of successive R-R-interval differences (RMSSD) from ECG recordings was used as time-domain measure of HF HRV. MRI scans were performed on a 3.0-T Siemens Magnetom Trio scanner. Cortical reconstruction and volumetric segmentation were performed with the Freesurfer image analysis suite, including 12 regions as regions of interests (ROI). Zero-order and partial correlations were used to assess the correlation of RMSSD with cortical thickness in selected ROIs. Lateral orbitofrontal cortex (OFC) cortical thickness was significantly associated with RMSSD. Further, both studies, in line with previous research, showed correlations between RMSSD and anterior cingulate cortex (ACC) cortical thickness. Meta-analysis on adjusted correlation coefficients from individual studies confirmed an association of RMSSD with the left rostral ACC and the left lateral OFC. Future longitudinal studies are necessary to trace individual trajectories in the association of HRV and brain structure across aging.